2006
DOI: 10.1021/la0531751
|View full text |Cite
|
Sign up to set email alerts
|

Photolithographically Patterned Surface Modification of Poly(dimethylsiloxane) via UV-Initiated Graft Polymerization of Acrylates

Abstract: Patterned surface modification of poly(dimethylsiloxane) (PDMS) is achieved by combining ultraviolet-initiated graft polymerization (UV-GP) and photolithography. Poly(acrylic acid) (PAA) and poly(methacrylic acid) (PMAA) patterns were grafted onto PDMS with micrometer-scale feature edge resolution. The morphology and chemical composition of the grafted layers were assessed by optical and atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), and XPS imaging. AFM section analyses demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 19 publications
1
28
1
Order By: Relevance
“…The UV cross-linked coating exhibited a contact angle of less than 20°, suggesting a hydrophilic surface as expected for a thin hydrogel layer of polyacrylic acid. These results are in contrast to the literature data [19,20] on adsorbed or plasma grafted poly(acrylic acid) layers, which show a contact angle of 45°-50° and suggest that the cross-linked poly(acrylic acid) coating behaves like thin hydrogel layers.…”
Section: Resultscontrasting
confidence: 99%
“…The UV cross-linked coating exhibited a contact angle of less than 20°, suggesting a hydrophilic surface as expected for a thin hydrogel layer of polyacrylic acid. These results are in contrast to the literature data [19,20] on adsorbed or plasma grafted poly(acrylic acid) layers, which show a contact angle of 45°-50° and suggest that the cross-linked poly(acrylic acid) coating behaves like thin hydrogel layers.…”
Section: Resultscontrasting
confidence: 99%
“…In order to reduce the analytes adsorption and improve the separation efficiency, it is essential to modify the surface of glass–PDMS hybrid chip. Many different strategies have been proposed to modify PDMS surface properties, such as physical treatment by oxygen plasma 26, 27 or UV light 28, surface grafting 29–31, and physically adsorbed coatings 32, 33. Generally, some of static surface modifications are time‐consuming, and not suitable for reversible sealed glass–PDMS hybrid chip.…”
Section: Resultsmentioning
confidence: 99%
“…[1,3,6,16] To make the surface of PDMS hydrophilic and maintain its elasticity, researchers have developed many methods, including physical adsorption, plasma treatment, plasma/ozone or UV/ozone oxidation, and surface grafting. [3,14,[17][18][19][20][21] However, it has been proved that only the PDMS modified by surface grafting can maintain its hydrophilicity for a long time, [22] those modified by other methods were suffered hydrophobicity recovery due to the weak interaction with adsorbates or blended polymers, or the flexibility of PDMS chains which will embed the hydrophilic layer of oxide into the bulk. However, it's very difficult to graft polymer brushes on the surface of PDMS since the grafted polymer chains easily penetrates the network of PDMS chains due to its high flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…However, it's very difficult to graft polymer brushes on the surface of PDMS since the grafted polymer chains easily penetrates the network of PDMS chains due to its high flexibility. Although there are a lot of work on tailoring the PDMS surface by sequentially grafting poly(acrylic acid) (PAA) chains initiated by surface adsorbed photoinitiators to modify the hydrophobic channels in PDMS fluidic microchips [3,20,21,23], they are focused on the improvement of the devices' performance. We and other peers have demonstrated that the trace of adsorbed photoinitiators affects the surface topography of the grafted PDMS films.…”
Section: Introductionmentioning
confidence: 99%